Purinergic P2X7 receptor expression increases in leukocytes from intra-abdominal septic patients - Martínez-Banaclocha, Helios; García-Palenciano, Carlos; Martínez-Alarcón, Laura; Amores-Iniesta, Joaquín; Martín-Sánchez, Fátima; Ercole, Giovanni A.; González-Lisorge, Ada; Fernández-Pacheco, José; Martínez-Gil, Piedad; Padilla-Rodríguez, Julio; Baroja-Mazo, Alberto; Pelegrín, Pablo; et al. (Frontiers in Immunology, 2023)
Inflammation is a tightly coordinated response of the host immune system to bacterial and viral infections, triggered by the production of inflammatory cytokines. Sepsis is defined as a systemic inflammatory response followed by immunosuppression of the host and organ dysfunction. This imbalance of the immune response increases the risk of mortality of patients with sepsis, making it a major problem for critical care units worldwide. The P2X7 receptor plays a crucial role in activating the immune system by inducing the activation of peripheral blood mononuclear cells. In this study, we analyzed a cohort of abdominal origin septic patients and found that the expression of the P2X7 receptor in the plasma membrane is elevated in the different subsets of lymphocytes. We observed a direct relationship between the percentage of P2X7-expressing lymphocytes and the early inflammatory response in sepsis. Additionally, in patients whose lymphocytes presented a higher percentage of P2X7 surface expression, the total lymphocytes populations proportionally decreased. Furthermore, we found a correlation between elevated soluble P2X7 receptors in plasma and inflammasome-dependent cytokine IL-18. In summary, our work demonstrates that P2X7 expression is highly induced in lymphocytes during sepsis, and this correlates with IL-18, along with other inflammatory mediators such as IL-6, IL-8, and procalcitonin.